A Novel Reversible Data Hiding Algorithm Based on Probabilistic XOR Secret Sharing in Wavelet Transform Domain - Avci, Engin; Tuncer, Turker; Avci, Derya (Springer Heidelberg, 2016)
In recent years, a lot of data hiding algorithms have been proposed in the literature. Providing high payload capacity, high visual quality, and robustness is the main aim of data hiding algorithms. However, high visual quality and high payload capacity are inversely proportional. For this reason, we used a probabilistic method. Probabilistic method is one of the soft computing methods. In this paper, a new data hiding algorithm based on probabilistic XOR secret sharing (PXORSS) in lifting wavelet transform (LWT) domain is proposed for providing high capacity and high visual quality. Previous studies have used cover images as RGB images or multiple grayscale images. LWT is proposed to use secret-sharing-based data hiding algorithms with a single grayscale cover image. In the proposed method, we used low-high (LH), high-low (HL), and high-high (HH) high-pass filter bands as cover images, and the secret data are divided into three secret shares by using PXORSS scheme. The least distorted pieces of probabilities are embedded into the high-pass filter bands as the secret share of the host image. We obtained high capacity and high visual quality in LWT domain by using the proposed method.
Keywords: Data hiding; Probabilistic XOR secret sharing; Lifting wavelet transform; Watermarking; Information security